Meta Analisis Efektivitas Model Discovery Learning terhadap Hasil Belajar Kognitif Siswa SD - Wahyu Ferdiansyah; Gamaliel Septian Airlanda (FONDATIA, 2021)
The research was conducted to understand the influence of discovery learning models on student cognitive learning outcomes. The development of a learning model is needed to improve the quality of students in school so that it can directly improve the learning outcomes of students, the application of less attractive learning models will make students feel bored and affect the learning outcomes of students be less than optimal. This study uses the Meta-Analysis design, Meta-Analysis in this study to examine the effectiveness of the Discovery Learning learning model on student cognitive learning outcomes. From the results of the analysis of 20 studies, it was found that the effect size obtained was 1.86, so it could be said that learning carried out using the Discovery Learning model affected improving cognitive learning outcomes of elementary school students.